2021
DOI: 10.1108/jiabr-05-2020-0171
|View full text |Cite
|
Sign up to set email alerts
|

Do academic and professional institutions promote the awareness and knowledge of Islamic banking and finance in Nigeria?

Abstract: Purpose The purpose of this study is to examine the contribution of academic and professional institutions in promoting the awareness and knowledge of Islamic banking and finance in Nigeria. Design/methodology/approach The data were generated through a documentary research method by examining the Benchmark Minimum Academic Standards (BMAS) for Nigerian universities and Nigerian university curricula for the relevant undergraduate programs, as well as examination syllabi and training brochures for the relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 26 publications
0
21
1
Order By: Relevance
“…For example, Richards and Safari (2021) used the archival data kept by Australia’s Parliamentary Joint Committee on Corporations and Financial Services and the Royal Commission into Misconduct in the Banking, Superannuation and Financial Services Industry with a view to assessing the extent to which financial planning is disclosed in Australia. Umar and Kurawa (2021) applied the documentary research method to justify the reasons why the awareness and knowledge of Islamic accounting standards for Islamic financial institutions are very low in Nigeria. Similarly, Umar et al (2021) applied the same method to explain the insignificant contributions of educational institutions and professional associations to spreading awareness and knowledge of Islamic banking and finance in Nigeria.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Richards and Safari (2021) used the archival data kept by Australia’s Parliamentary Joint Committee on Corporations and Financial Services and the Royal Commission into Misconduct in the Banking, Superannuation and Financial Services Industry with a view to assessing the extent to which financial planning is disclosed in Australia. Umar and Kurawa (2021) applied the documentary research method to justify the reasons why the awareness and knowledge of Islamic accounting standards for Islamic financial institutions are very low in Nigeria. Similarly, Umar et al (2021) applied the same method to explain the insignificant contributions of educational institutions and professional associations to spreading awareness and knowledge of Islamic banking and finance in Nigeria.…”
Section: Methodsmentioning
confidence: 99%
“…Umar and Kurawa (2021) applied the documentary research method to justify the reasons why the awareness and knowledge of Islamic accounting standards for Islamic financial institutions are very low in Nigeria. Similarly, Umar et al (2021) applied the same method to explain the insignificant contributions of educational institutions and professional associations to spreading awareness and knowledge of Islamic banking and finance in Nigeria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contrasting perceptions and insights between Islamic Microfinance Institutions show the need to place sharia governance as the main course in higher education. In line with the opinion of Umar et al (2021), it was found that Islamic banking and finance issues have not received special attention to the extent that awareness and knowledge will be promoted. Universities can see the potential of developing student knowledge and insights for the future of students themselves and also universities.…”
Section: Conclusion and Suggestionsmentioning
confidence: 83%
“…From the previous findings, insights regarding SG need to be considered. So this study aims to evaluate and According to Umar et al (2021), nature of this, academic and professional institutions can play an important role in promoting awareness and knowledge of Islamic banking and finance.…”
Section: Introductionmentioning
confidence: 99%